Mid-Neoproterozoic tectonic evolution of the northern margin of the Yangtze Block, South China: New insights from high-temperature magma events - Huang, Chang-Cheng; Zou, Hao; Bagas, Leon; Chen, Hai-Feng; Xiao, Bin; Jiang, Xiu-Wei; Li, Min; Hu, Cheng-Hui; Yu, Li-Ming (Lithos, 2022)
Numerous Neoproterozoic intrusive rocks are distributed along the northern margin of the Yangtze Block in South China, and their petrogenesis and tectonic setting remain the subject of debate. This study systematically compiled data from igneous rocks from the northern margin of the Yangtze Block, including abundant felsic plutons with formed temperatures of >800 °C. The data reveal two high-temperature rifting-related events at ~830–780 and 750–700 Ma. Significant changes in Hf-O isotopes appeared at ~790 Ma, with later rocks exhibiting positive εHf(t) and low δ18O. To clarify the nature and tectonic significance of these high-temperature events, we sampled plutonic rocks from the Lianghekou (LHK) and Dalanggou (DLG) areas of Hannan, on the northern margin of the Yangtze Block. The samples from LHK are ~785 Ma monzogranite emplaced towards the end of the first high-temperature event and derived from partial melting of thickened juvenile crust contaminated by older crustal material. These rocks have εHf (t) values between +4.6 and + 11.5, δ18O values between +6.2‰ and + 7.3‰, and contain residual combinations of garnet, clinopyroxene, rutile, and amphibole. The genesis of the monzogranite is interpreted as being emplaced in an initial rifting environment and related to a super mantle plume. The DLG samples are ~743 Ma alkali feldspar granite representing the second event; they have the geochemical characteristics of a reduced A-type granite enriched in Fe and poor in Mg, FeOT/(FeOT + MgO) values close to 1, and emplacement temperatures of 813 °C–848 °C. The alkali feldspar granite originated from partial melting of a tholeiitic source and was influenced by extensive fractionation. It has εHf(t) values of +2.5 to +10.9, δ18O values of +6.6‰ to +7.4‰, and contains residual plagioclase. The DLG alkali feldspar granite and nearby reduced A-type granite indicate that the northern margin of the Yangtze Block experienced a low oxygen fugacity environment at ~817–743 Ma. The second high-temperature event possibly reflected rifting that gradually matured after 790 Ma, at which point the mantle changed from a source of heat alone into a source of both heat and material. •Two high-T magma events related to rifting.•Hf-O isotopes between the two high-T magma events are distinct.•The first high-T magma event was caused by initial rift related to a mantle plume.•The second event was influenced by a more mature rift related to the mantle plume.